Ensemble programme for early intervention in informal caregivers of psychiatric adult patients: a protocol for a randomised controlled trial - Daniel Wenger; Shyhrete Rexhaj; Shadya Monteiro; Philippe Golay; Claire Coloni-Terrapon; Jérôme Favrod (BMJ Open)
Introduction Informal caregivers play a major role in the support and maintenance of community patients with severe psychiatric disorders. A pilot study showed that an individualised brief intervention such as the Ensemble programme leads to significant improvements in psychological health state and optimism.Methods and analysis This randomised controlled trial aims to compare the efficacy of using Ensemble in improving informal caregivers’ psychological health states and the ability to play an active role in their situations with that of support as usual. Improvements on the psychological health global index will be measured three times (T0-pre, T1-post and T3 2 months follow) with standardised questionnaires (the Global Severity Index of Brief Inventory Symptoms, the Life Orientation Test-Revised, the 36-item Medical Outcome Study Short-Form Health Survey and the French Zarit Burden Interview). Differences between groups in post-test and pretest values will be examined using an analysis of covariance for each outcome variable. The severity of illness measured by the Social and Occupational Functioning Assessment Scale will also be collected at T0 and T2 to compare eventual patient improvements. At the end of the programme, the experiences of the 20 patients participating in the Ensemble programme will be evaluated qualitatively.Ethics and dissemination The research protocol received full authorisation from the Human Research Ethics Committee of the Vaud state, Switzerland. The principal paper will concern the results of the experimental design used to test the Ensemble programme. The research team will prioritise open access publications.Trial registration number NCT04020497